Designing method for educational environment in the system of continuous pedagogical education - M.G, Sergeeva; D.N, Belova; Suslennikova E.Е, Nikolaeva M.V., (Opción, 2020)
The trend of development of the information and communication environment is the transfer of individual activity to the Internet: professional activities mediated by remote technologies; the development of social networks-communities, personal websites, blogs, twitters; scientific, educational, and artistic publications; viewing news, movies, concerts, meetings, etc. In this context, the dual social role of a professional teacher as a provider and, at the same time, a consumer of educational services is highlighted. Meeting the needs of the education system the teacher is able to implement innovative changes in the educational process, requires a fundamentally new technological support of innovation and expects the teachers’ knowledge of the relevant standards of innovative behavior and description of models.